Seri Rama and Maharaja Wana in Wayang Kulit Kelantan: Visual Analysis of Their Puppets - Wong, Fiona E Chiong (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Wayang Kulit Kelantan, currently one of the two remaining shadow play forms in Malaysia, remains active in the northern part of peninsular Malaysia in particular the state of Kelantan, up till southern part of Thailand. It performs mainly a localized Malay folk version Hikayat Maharaja Wana derived from the famous Indian epic Ramayana, in contrast to the other literary version Hikayat Seri Rama. The origin of Wayang Kulit Kelantan, although much has been debated, could have possibly derived from the pre-Islamic or archetypal prototype of Wayang Kulit Purwa of Java, following the Majapahit Empire’s collapse and the spread of Islam on that island in the 16th century (Ghulam-Sarwar, 2004, pp. 61-62). The introduction of the legendary nine saints (wali Songo) in Java (Ghulam-Sarwar, 1994, pp. 274-275) led to the migration of this proto shadow play from Java to Bali and other Indonesian islands as well as the Malay Peninsula. Strong influences of animism, Hinduism, traditional Javanese beliefs and Islam are evident in Wayang Kulit Kelantan performances (Ghulam-Sarwar, 1993, pp. 4-5), as well as in the conception of the epic’s characters and their visualization on leather puppets.;